Serotonergic and dopaminergic control of impulsivity in gambling disorder - Kaasinen Valtteri; Honkanen Emma A.; Lindholm Kari; Jaakkola Elina; Majuri Joonas; Parkkola Riitta; Noponen Tommi; Vahlberg Tero; Voon Valerie; Clark Luke; Joutsa Juho; Seppänen Marko (WILEY, 2025)
Gambling disorder (GD) is major public health issue. The disorder is often characterized by elevated impulsivity with evidence from analogous substance use disorders underlining prominent roles of brain monoamines in addiction susceptibility and outcome. Critically, GD allows the study of addiction mechanisms without the confounder of the effects of chronic substances. Here, we assessed the roles of striatal dopamine transporter binding and extrastriatal serotonin transporter binding in GD as a function of impulsivity using [I-123]FP-CIT SPECT imaging in 20 older adults with GD (DSM-5 criteria; mean age 64 years) and 40 non-GD age- and sex-matched controls. We focused on GD in older individuals because there are prominent age-related changes in neurotransmitter function and because there are no reported neuroimaging studies of GD in older adults. Volume-of-interest-based and voxelwise analyses were performed. GD patients scored clearly higher on impulsivity and had higher tracer binding in the ventromedial prefrontal cortex than controls (p < 0.001), likely reflecting serotonin transporter activity. The binding in the medial prefrontal cortex positively correlated with impulsivity over the whole sample (r = 0.62, p < 0.001) as well as separately in GD patients (r = 0.46, p = 0.04) and controls (r = 0.52, p < 0.001). Striatal tracer binding, reflecting dopamine transporter activity was also positively correlated with impulsivity but showed no group differences. These findings highlight the role of prefrontal serotonergic function in GD and impulsivity. They identify cerebral coordinates of a potential target for neuromodulation for both GD and high impulsivity, a core phenotypic dimensional cognitive marker in addictions.